Preparation method of halide spinel type positive electrode composite material

By preparing halide spinel type positive electrode composites, the problems of low ionic conductivity and high cost of positive electrode composites in all-solid-state batteries are solved, high energy density and excellent interface compatibility are achieved, and good industrial application potential is good.

CN119764313APending Publication Date: 2025-04-04YANGTZE DELTA REGION INST (QUZHOU) UNIV OF ELECTRONIC SCI & TECH OF CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411948856.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the existing all-solid-state battery positive electrode composite materials, the ionic conductivity is low and the cost is high, resulting in a decrease in energy density, and the compatibility and interface side reaction problems with halide electrolytes need to be solved urgently.

Method used

A method for preparing a halide spinel type positive electrode composite material is adopted. By weighing LiCl and FeCl2 raw materials in the form of Li2-xFe1+x/2Cl4 under the protection of argon atmosphere, the halide spinel type positive electrode active material with high ionic conductivity is prepared by mechanical ball milling, pressing, annealing and uniformly mixing with conductive agents and solid electrolytes.

Benefits of technology

It realizes a low-cost, high ionic conductivity positive electrode composite material, excellent interface compatibility and high specific capacity, effectively improving the energy density and rate performance of all-solid-state batteries, and has good industrial production prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764313A_ABST
    Figure CN119764313A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a halide spinel type positive electrode composite material, which comprises the following steps: S1, weighing LiCl and FeCl2 raw materials according to the molar ratio of Li < 2-x > Fe < 1 + x > / 2Cl4 in the form of Li < 2-x > Fe < 1 + x > / 2Cl4 under the protection of argon atmosphere to obtain powder A; s2, performing mechanical ball milling on the powder A to obtain powder B; s3, pressing the powder B into a sheet under a certain pressure to obtain a solid C; s4, the solid C is subjected to annealing treatment in the argon atmosphere or under the vacuum condition, and a solid D is obtained; s5, uniformly mixing the solid D, a conductive agent and a solid electrolyte by using a hand milling or low-speed ball milling method to obtain a positive electrode composite material of the all-solid-state battery, namely powder E; and S6, placing the solid electrolyte in a mold for tabletting, placing the powder E at one end of the mold for tabletting under a certain pressure, and finally placing a negative electrode material at the other end of the mold to assemble the all-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid-state lithium batteries, and in particular relates to a method for preparing a halide spinel positive electrode composite material. Background Art

[0002] As the development direction of the next generation of battery technology, all-solid-state battery technology has attracted much attention for its application prospects in electric vehicles and large-scale energy storage. First, in all-solid-state batteries, the cathode composite material usually contains three parts: cathode active material, solid electrolyte, and conductive carbon. Among them, the solid electrolyte and conductive carbon are only responsible for the transmission of ions and electrons in the cathode, and do not contribute to the capacity. If a large amount of solid electrolyte and conductive carbon are relied on, the overall energy density of the battery will be seriously reduced (Toward high performance all-solid-state lithium batteries with high-voltage cathode materials: design strategies for solid electrolytes, cathode interfaces, and composite electrodes [J]. Advanced Energy Materials, 2021, 11 (28): 2003154). Secondly, in the selection of cathode active materials, traditional lithium cobalt oxide and ternary cathode materials have attracted much attention due to their high theoretical specific capacity, but these materials contain expensive and rare metals, which is not conducive to sustainable development. In addition, the ionic conductivity of these cathode materials themselves is low, resulting in the need to rely on a large amount of electrolyte in the cathode component to achieve ion conduction, which not only increases the cost but also reduces the energy density of the entire battery. At the same time, the compatibility of these oxide cathode materials with halide electrolytes and interfacial side reactions are also technical challenges that need to be solved urgently. In order to solve the above problems, Chen et al. (Low-cost iron trichloride cathode for all-solid-state lithium-ion batteries[J].Nature Sustainability,2024:1-9.) proposed FeCl 3 The cost of positive electrode active materials used in all-solid-state batteries is only 2% of that of lithium iron phosphate. Moreover, its application in all-solid-state batteries effectively solves the problem of active material dissolution in liquid batteries, ensuring structural stability and interface compatibility. However, FeCl 3 The positive electrode itself does not contain ions, so the ionic conductivity is extremely poor, and a large amount of solid electrolyte is still required in the positive electrode component to maintain lithium ion transmission. Zhang et al. (Li 2.9 Fe 0.9Zr 0.1 Cl 6 Li was proposed as Redox-Active Catholyte for Solid-State Li-Ion Batteries[J]. Chemistry of Materials, 2024, 36(20):10104-12. 2.9 Fe 0.9 Zr 0.1 Cl 6 The positive electrode conductive agent not only has high ionic conductivity and plays a role in lithium ion conduction in the positive electrode components, but also provides capacity for the positive electrode active material, effectively increasing the specific capacity of the positive electrode. However, the theoretical specific capacity of the positive electrode conductive agent is relatively low, about 70 mAh g -1 , which is far lower than the specific capacity of traditional positive electrode active materials, and will also reduce the energy density of the entire battery. Summary of the invention

[0003] The purpose of the present invention is to solve the above problems and provide a method for preparing a halide spinel positive electrode composite material with low cost, high abundance and high ion conductivity.

[0004] In order to solve the above technical problems, the technical solution of the present invention is: a method for preparing a halide spinel positive electrode composite material, comprising the following steps:

[0005] S1. Under argon atmosphere protection, according to Li 2-x Fe 1+x / 2 Cl 4 In the form of, weigh LiCl and FeCl according to their molar ratio 2 Raw materials, powder A is obtained;

[0006] S2, mechanically ball-milling powder A to obtain powder B;

[0007] S3, pressing powder B into a sheet under a certain pressure to obtain solid C;

[0008] S4, annealing the solid C in an argon atmosphere or under vacuum conditions to obtain a solid D;

[0009] S5, uniformly mixing the solid D with the conductive agent and the solid electrolyte by hand milling or low-speed ball milling to obtain a positive electrode composite material for an all-solid-state battery, namely, powder E;

[0010] S6. First, place the above-mentioned solid electrolyte in a mold to press a tablet, then place powder E at one end of the mold to press a tablet under a certain pressure, and finally place the negative electrode material at the other end of the mold to assemble into an all-solid-state battery.

[0011] Preferably, Li in S1 2-x Fe 1+x / 2 Cl 4 Chemical formula, where x ranges from 0 to 0.5.

[0012] Preferably, the mechanical ball milling parameters in S2 are as follows: the ball-to-material mass ratio of the mechanical ball milling is 30-60:1, the ball milling time is 10-60 hours to ensure sufficient mixing and reaction; the ball milling speed is 500-1000 rpm; the ionic conductivity of powder B is ≥1×10 -8 S / cm.

[0013] Preferably, the pressure in S3 is 30000-50000N, the tableting time is 3-8min, and the tableting is performed under the protection of argon.

[0014] Preferably, the conditions for the annealing treatment in S4 are: under the protection of argon atmosphere or under vacuum conditions, the sintering temperature is 300-400°C, the sintering time is 5-10 hours, and then naturally cooled to room temperature; the crystal structure of solid D is spinel type, and the specific space groups include Fd-3m, Cmmm and Imma; the ionic conductivity of solid D is not less than 1×10-5S / cm.

[0015] Preferably, the conductive agent in S5 can be selected from any one, including but not limited to: acetylene black, graphene, carbon nanotubes, carbon nanofibers; the mass fraction of the conductive agent in the powder E is 3-10%.

[0016] Preferably, the solid electrolyte in S5 can be selected from any one, including but not limited to: Li 3 YC 6 , Li 3 InCl 6 , Li 6 PS 5 Cl, the mass fraction of the solid electrolyte in the powder E is 0 to 50%.

[0017] Preferably, the hand milling time in S5 is 30 to 60 min, the low-speed ball milling time is 20 to 40 min, and the rotation speed is 200 to 400 rpm.

[0018] Preferably, the powder E in S5 is black in color and has a particle size of ≤1 μm.

[0019] Preferably, the solid electrolyte and the positive electrode in S6 are pressed into tablets separately, with a pressure of 20000-30000N and a pressing time of 2-4min; the negative electrode material can be any one, including but not limited to lithium metal, lithium indium alloy, graphite, and silicon carbon.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention provides a method for preparing a halide spinel cathode composite material. By optimizing the spinel structure, utilizing its high ionic conductivity characteristics, and combining low-cost, environmentally friendly, and abundant raw materials, the solid phase preparation technology is used to successfully prepare Li 2-x Fe 1+x / 2 Cl 4 (x=0~0.5) halogenated spinel positive electrode active material, only 3~10wt% conductive carbon is added to the positive electrode active material to be used as the positive electrode of the all-solid-state battery and shows excellent interfacial compatibility when matched with the halide electrolyte. These characteristics make the halide positive electrode active material an ideal choice for promoting the development and commercialization of all-solid-state battery technology.

[0022] 2. A method for preparing a halide spinel positive electrode composite material of the present invention prepares a new halide spinel positive electrode active material, which has good ionic conductivity at room temperature, and the ionic conductivity is not less than 1×10 -5 S / cm. The positive electrode composite material formed by adding 5-10wt% conductive carbon to the prepared active material can be directly used as the positive electrode of the all-solid-state battery, and the redox voltage is about 3.7V, which effectively solves the problem of high electrolyte content in the positive electrode composite material of the traditional all-solid-state battery reducing the energy density of the battery. The composite material formed by adding 5-10wt% conductive carbon and 20-50wt% solid electrolyte to the prepared active material can be used as the positive electrode of the all-solid-state battery. The composed all-solid-state battery has an ultra-high rate performance of 1-10C, the required material cost is low, the preparation process is simple, it can meet the requirements of large-scale production, and has good prospects for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is the ionic conductivity of the halide spinel positive electrode active material obtained by the method for preparing the halide spinel positive electrode composite material of the present invention;

[0024] Figure 2 The charge and discharge curve of an all-solid-state battery assembled with the halogenated spinel positive electrode composite material prepared by the present invention. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments:

[0026] Embodiment 1

[0027] like Figure 1 and Figure 2 As shown, the present invention provides a method for preparing a halide spinel positive electrode composite material, comprising the following steps:

[0028] S1. Under argon atmosphere protection, according to Li 2-x Fe 1+x / 2 Cl 4 In the form of, weigh LiCl and FeCl according to their molar ratio 2 Raw materials, powder A was obtained.

[0029] In step S1, Li 2-x Fe 1+x / 2 Cl 4 Chemical formula, where x ranges from 0 to 0.5.

[0030] In this embodiment, S1, under argon protection, accurately weigh 0.40094g of LiCl and 0.59906g of FeCl according to the molar ratio of the halide solid positive electrode active material. 2 Raw materials, powder A was obtained.

[0031] S2. Powder A is mechanically ball-milled to obtain powder B.

[0032] The mechanical milling parameters in step S2 are as follows: the ball-to-material mass ratio of the mechanical milling is 30-60:1, the milling time is 10-60 hours to ensure sufficient mixing and reaction; the milling speed is 500-1000 rpm; the ionic conductivity of powder B is ≥1×10 -8 S / cm.

[0033] In this embodiment, S2, powder A is mechanically ball-milled, the ball-to-material mass ratio of the mechanical ball milling is precisely 60:1, and the ball milling time is controlled at 10 hours to ensure sufficient mixing and reaction; the ball milling speed is controlled at 500 revolutions per minute (rpm) to obtain powder B.

[0034] S3. Press powder B into a sheet under a certain pressure to obtain solid C.

[0035] The pressure in step S3 is 30000-50000N, the tableting time is 3-8min, and the tableting is performed under the protection of argon.

[0036] In this embodiment, S3, powder B is pressed into tablets. The pressing pressure is 3 tons, and the tableting time is 5 minutes to obtain solid C.

[0037] S4. Annealing solid C in an argon atmosphere or under vacuum conditions to obtain solid D.

[0038] The conditions for the annealing treatment in step S4 are: under the protection of argon atmosphere or under vacuum conditions, the sintering temperature is 300-400°C, the sintering time is 5-10 hours, and then naturally cooled to room temperature; the crystal structure of solid D is spinel type, and the specific space groups include Fd-3m, Cmmm and Imma; the ionic conductivity of solid D is not less than 1×10-5S / cm.

[0039] In this embodiment, S4, the solid C is annealed under the protection of an inert atmosphere, the sintering temperature is controlled at 350 degrees Celsius, the sintering time is 5 hours, and then naturally cooled to room temperature to obtain a halide positive electrode active material.

[0040] S5. Evenly mix the solid D with the conductive agent and the solid electrolyte by hand milling or low-speed ball milling to obtain the positive electrode composite material of the all-solid-state battery, namely, powder E.

[0041] The conductive agent in step S5 can be any one, including but not limited to: acetylene black, graphene, carbon nanotubes, carbon nanofibers; the mass fraction of the conductive agent in the powder E is 3-10%. The solid electrolyte in step S5 can be any one, including but not limited to: Li 3 YC 6 , Li 3 InCl 6 , Li 6 PS 5 Cl, the mass fraction of the solid electrolyte in the powder E is 0-50%. The hand milling time in step S5 is 30-60 min, the low-speed ball milling time is 20-40 min, and the rotation speed is 200-400 rpm. The powder E in step S5 is black in color, and the powder particle size should be ≤1 μm.

[0042] S6. First, place the above-mentioned solid electrolyte in a mold to press a tablet, then place powder E at one end of the mold to press a tablet under a certain pressure, and finally place the negative electrode material at the other end of the mold to assemble into an all-solid-state battery.

[0043] In step S6, the solid electrolyte and the positive electrode are pressed separately, the pressure is 20000-30000N, and the pressing time is 2-4min; the negative electrode material can be any one, including but not limited to lithium metal, lithium indium alloy, graphite, silicon carbon.

[0044] Embodiment 2

[0045] Compared with the first embodiment, the differences of this embodiment are as follows:

[0046] S1. Under argon protection, accurately weigh 0.379g of LiCl and 0.6201g of FeCl according to the molar ratio of the halide solid positive electrode active material. 2 Raw materials, powder A was obtained.

[0047] S2. Powder A was mechanically ball-milled, and the ball-to-material mass ratio of the mechanical ball milling was precisely 60:1. The ball milling time was controlled within 10 hours to ensure sufficient mixing and reaction; the ball milling speed was controlled at 500 revolutions per minute (rpm) to obtain powder B.

[0048] S3. Powder B is pressed into tablets at a pressing pressure of 3 tons and a tableting time of 5 minutes to obtain solid C.

[0049] S4. Annealing the solid C under the protection of an inert atmosphere, controlling the sintering temperature at 350 degrees Celsius, and sintering time for 5 hours, and then naturally cooling to room temperature to obtain a halide positive electrode active material.

[0050] The rest of this embodiment is the same as that of the first embodiment.

[0051] Embodiment 3

[0052] Compared with the first embodiment, the differences of this embodiment are as follows:

[0053] S1. Under argon protection, accurately weigh 0.3824g of LiCl and 0.61763g of FeCl according to the molar ratio of the halide solid positive electrode active material. 2 Raw materials, powder A was obtained.

[0054] S2. Powder A was mechanically ball-milled, and the ball-to-material mass ratio of the mechanical ball milling was precisely 60:1. The ball milling time was controlled within 10 hours to ensure sufficient mixing and reaction; the ball milling speed was controlled at 500 revolutions per minute (rpm) to obtain powder B.

[0055] S3. Powder B is pressed into tablets at a pressing pressure of 3 tons and a tableting time of 5 minutes to obtain solid C.

[0056] S4. Annealing the solid C under the protection of an inert atmosphere, controlling the sintering temperature at 350 degrees Celsius, and sintering time for 5 hours, and then naturally cooling to room temperature to obtain a halide positive electrode active material.

[0057] The rest of this embodiment is the same as that of the first embodiment.

[0058] Embodiment 4

[0059] Compared with the first embodiment, the differences of this embodiment are as follows:

[0060] S1. Under argon protection, accurately weigh 0.3538g of LiCl and 0.6462g of FeCl according to the molar ratio of the halide solid positive electrode active material. 2 Raw materials, powder A was obtained.

[0061] S2. Powder A was mechanically ball-milled, and the ball-to-material mass ratio of the mechanical ball milling was precisely 60:1. The ball milling time was controlled within 10 hours to ensure sufficient mixing and reaction; the ball milling speed was controlled at 500 revolutions per minute (rpm) to obtain powder B.

[0062] S3. Powder B is pressed into tablets at a pressing pressure of 3 tons and a tableting time of 5 minutes to obtain solid C.

[0063] S4. Annealing the solid C under the protection of an inert atmosphere, controlling the sintering temperature at 350 degrees Celsius, and sintering time for 5 hours, and then naturally cooling to room temperature to obtain a halide positive electrode active material.

[0064] The rest of this embodiment is the same as that of the first embodiment.

[0065] Embodiment 5

[0066] Compared with the first embodiment, the differences of this embodiment are as follows:

[0067] S1. Under argon protection, accurately weigh 0.3310g of LiCl and 0.6692g of FeCl according to the molar ratio of the halide solid positive electrode active material. 2 Raw materials, powder A was obtained.

[0068] S2. Powder A was mechanically ball-milled, and the ball-to-material mass ratio of the mechanical ball milling was precisely 60:1. The ball milling time was controlled within 10 hours to ensure sufficient mixing and reaction; the ball milling speed was controlled at 500 revolutions per minute (rpm) to obtain powder B.

[0069] S3. Powder B is pressed into tablets at a pressing pressure of 3 tons and a tableting time of 5 minutes to obtain solid C.

[0070] S4. Annealing the solid C under the protection of an inert atmosphere, controlling the sintering temperature at 350 degrees Celsius, and sintering time for 5 hours, and then naturally cooling to room temperature to obtain a halide positive electrode active material.

[0071] The rest of this embodiment is the same as that of the first embodiment.

[0072] Embodiment 6

[0073] Compared with the first embodiment, the differences of this embodiment are as follows:

[0074] S5. Grind the positive electrode active material prepared in the above Example 2 by hand to make it uniformly mixed with the solid electrolyte or conductive carbon. The hand grinding time is 30 to 60 minutes to obtain a positive electrode composite material. The solid electrolyte can be Li 3 YC 6The solid electrolyte accounts for 45% of the powder E by mass, and the conductive carbon is acetylene black, and the conductive carbon accounts for 5% of the powder E by mass. In this embodiment, the conductive agent is conductive carbon.

[0075] S6. First, place the above solid electrolyte in a mold and compress it into a tablet, then place the positive electrode composite material at one end of the mold and compress it under a certain pressure, and finally place the negative electrode material at the other end of the mold to assemble into a full solid-state battery. The negative electrode material is lithium metal.

[0076] The rest of this embodiment is the same as that of the first embodiment.

[0077] The positive electrode composite material prepared by the present invention has a strength of ≥1×10 -5 The ultra-high ionic conductivity of S / cm is prepared by ball milling annealing method, aiming to reduce the cost of all-solid-state battery positive electrode composite materials. Compared with traditional all-solid-state battery positive electrode composite materials, the active material of the present invention does not need to add ion conductive agents, and only 3-10wt% of electronic conductive agents are required to form positive electrode composite materials. The material has price cost advantages, low raw material cost, simple preparation process, and effectively reduces the cost of all-solid-state battery positive electrode composite materials. The addition of ion conductive agents can improve ionic conductivity and ensure excellent rate performance (up to 10C) and excellent cycle stability in all-solid-state batteries. The positive electrode composite material of the present invention not only reduces production costs and reduces environmental impact, but also shows great potential for industrial application. It is an ideal choice for promoting the development and commercialization of all-solid-state battery technology.

[0078] Those skilled in the art will appreciate that the embodiments described herein are intended to help readers understand the principles of the present invention, and should be understood that the protection scope of the present invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific variations and combinations that do not deviate from the essence of the present invention based on the technical revelations disclosed by the present invention, and these variations and combinations are still within the protection scope of the present invention.

Claims

1. A method for preparing a halide spinel positive electrode composite material, characterized in that: The following steps are involved: S1. Under argon atmosphere protection, according to Li 2-x Fe 1+x / 2 Cl4, weigh LiCl and FeCl2 raw materials according to their molar ratio to obtain powder A; S2, mechanically ball-milling powder A to obtain powder B; S3, pressing powder B into a sheet under a certain pressure to obtain solid C; S4, annealing the solid C in an argon atmosphere or under vacuum conditions to obtain a solid D; S5, uniformly mixing the solid D with the conductive agent and the solid electrolyte by hand milling or low-speed ball milling to obtain a positive electrode composite material for an all-solid-state battery, namely, powder E; S6. First, place the above-mentioned solid electrolyte in a mold to press a tablet, then place powder E at one end of the mold to press a tablet under a certain pressure, and finally place the negative electrode material at the other end of the mold to assemble into an all-solid-state battery.

2. The method for preparing a halide spinel positive electrode composite material according to claim 1, characterized in that: The Li in S1 2-x Fe 1+x / 2 Cl4 chemical formula, where x ranges from 0 to 0.

5.

3. The method for preparing a halide spinel positive electrode composite material according to claim 1, characterized in that: The mechanical milling parameters in S2 are as follows: the ball-to-material mass ratio of the mechanical milling is 30-60:1, the milling time is 10-60 hours to ensure sufficient mixing and reaction; the milling speed is 500-1000 rpm; the ionic conductivity of powder B is ≥1×10 -8 S / cm.

4. The method for preparing a halide spinel positive electrode composite material according to claim 1, characterized in that: The pressure in S3 is 30000-50000N, the tableting time is 3-8min, and the tableting is performed under the protection of argon.

5. The method for preparing a halide spinel positive electrode composite material according to claim 1, characterized in that: The conditions for the annealing treatment in S4 are: under the protection of argon atmosphere or vacuum conditions, the sintering temperature is 300-400°C, the sintering time is 5-10 hours, and then naturally cooled to room temperature; the crystal structure of solid D is spinel type, and the specific space groups include Fd-3m, Cmmm and Imma; the ionic conductivity of solid D is not less than 1×10-5S / cm.

6. The method for preparing a halide spinel positive electrode composite material according to claim 1, characterized in that: The conductive agent in S5 may be any one, including but not limited to: acetylene black, graphene, carbon nanotubes, carbon nanofibers; the mass fraction of the conductive agent in the powder E is 3-10%.

7. The method for preparing a halide spinel positive electrode composite material according to claim 1, characterized in that: The solid electrolyte in S5 may be any one, including but not limited to: Li3YCl6, Li3InCl6, Li6PS5Cl, and the mass fraction of the solid electrolyte in the powder E is 0 to 50%.

8. The method for preparing a halide spinel positive electrode composite material according to claim 1, characterized in that: The hand milling time in S5 is 30 to 60 minutes, the low-speed ball milling time is 20 to 40 minutes, and the rotation speed is 200 to 400 rpm.

9. The method for preparing a halide spinel positive electrode composite material according to claim 1, characterized in that: The powder E in S5 is black in color and has a particle size of ≤1 μm.

10. The method for preparing a halide spinel positive electrode composite material according to claim 1, characterized in that: The solid electrolyte and the positive electrode in S6 are pressed into tablets respectively, with a pressure of 20000-30000N and a pressing time of 2-4min; the negative electrode material can be any one, including but not limited to lithium metal, lithium indium alloy, graphite, and silicon carbon.

Citation Information

Patent Citations

  • Chloride solid electrolyte with stable conductivity and preparation method thereof

    CN112928326A

  • Halide-based positive electrode active material as well as synthesis method and application thereof

    CN116799201A

  • Cubic lithium-iron chloride crystal, method for producing the same and lithium secondary battery by using the same

    JP2001328816A

  • Anode active materials and manufacturing method thereof, and anode and lithium battery using the same

    KR1020130118756A